KARAKTERISTIK PAPAN PARTIKEL DARI BULU DOMBA, SERBUK GERGAJI DAN SERUTAN KAYU DENGAN PEREKAT UREA FORMALDEHIDA - M. I. Iskandar; Achmad Supriadi (Universitas Nusa Bangsa, 2015)
Particle Board Characteristics of Fur Sheep, Sawdust and Wood Shavings with Urea Formaldehyde Adhesive Particle board is a board made of particles of wood or other berlignoselulosa bonded with adhesive, then felted heat. Particle board excess, which uses industrial waste materials, uniform size and density, uniform thick and density, the character and quality can be set. This study aims to investigate the characteristics of particle board from sheep's wool, sawdust and wood shavings. The experimental design used was completely randomized design (CRD) with two factors and repeated three times. The first factor combination of pollen fleece (B), with sawdust sengon (G) and wood shavings sengon (S), namely B0G60S40 : (0% : 60% : 40%), B10G50S40 : (10% : 50% : 40%), B20G40S40 : (20% : 40% : 40%), B30G30S40 : (30% : 30% : 40% and the second factor consists of the physical properties (density, moisture content, thickness swelling and water absorption) and character of mechanical factor (flexural strength, modulus of elasticity, perpendicular and surface strength and straight screw holding). The results of the research were to produce a density value was between 0.69 to 0.78 g/cm3, water content with an average of 6.49%, a value between 32.36 to 83.9% thickness swelling, water absorption between 89,04- 169.15%, the flexural strength values between 68.4 to 121.8 kgf/cm2, elastic modulus was between 671.84 to 1381.51 kgf/cm2, the value of tensile strength perpendicular of the surface was between 0.44 to 1.3 kgf/cm2and screw holding strength value was between 6.0 to 22.3 kg. the higher use of powder fleece might degrade the quality of particle board, otherwise use the higher adhesive could improve the quality of particle board. The study of particle board and fleece, saws and wood shavings was on average below of the national Indonesia standard, except for the density and moisture content, for flexural strength was only partially standard value.Key words: fleece, characteristics, particle board, sawdust, wood shavings. ABSTRAK Papan partikel merupakan suatu papan yang terbuat dari partikel-partikel kayu atau bahan berlignoselulosa lainnya yang diikat dengan perekat, kemudian dikempa panas. Kelebihan papan partikel, yaitu menggunakan bahan limbah industri, ukuran dan kerapatan seragam, tebal dan kerapatan seragam, sifat dan kualitasnya dapat diatur. Penelitian ini bertujuan untuk mengetahui karakteristik papan partikel dari bulu domba, serbuk gergaji dan serutan kayu. Rancangan percobaan yang digunakan adalah Rancangan Acak Lengkap (RAL) pola faktorial dengan dua faktor dan ulangan sebanyak tiga kali. Faktor pertama kombinasi serbuk bulu domba (B), dengan serbuk gergaji kayu sengon (G) dan serutan kayu sengon (S), yaitu B0G60S40 : (0% : 60% : 40%), B10G50S40 : (10% : 50% : 40%), B20G40S40 : (20% : 40% : 40%), B30G30S40 : (30% : 30% : 40%) dan faktor kedua terdiri dari sifat fisis (kerapatan, kadar air, pengembangan tebal dan daya serap air) dan sifat mekanis (kuat lentur, modulus elastisitas, kuat tarik tegal lurus permukaan dan kuat pegang sekrup). Hasil penelitian menghasilkan nilai kerapatan antara 0,69-0,78 g/cm3, nilai kadar air dengan rata-rata 6,49%, nilai pengembangan tebal antara 32,36-83,9%, daya serap air antara 89,04-169,15%, nilai kuat lentur antara 68,4-121,8 kgf/cm2, nilai modulus elastisitas antara 671,84-1381,51 kgf/cm2, nilai kuat tarik tegak lurus permukaan antara 0,44-1,3 kgf/cm2 dan nilai kuat pegang sekrup antara 6,0-22,3 kg. penggunakan serbuk bulu domba yang semakin tinggi dapat menurunkan kualitas papan partikel, sebaliknya penggunaan perekat yang semakin tinggi dapat meningkatkan kualitas papan partikel. Penelitian papan partikel dan bulu domba, gergaji dan serutan kayu rata-rata di bawah standar nasional Indonesia, kecuali untuk kerapatan dan kadar air, untuk kuat lentur hanya sebagian yang masuk standar.Kata kunci : bulu domba, karakteristik, papan partikel, serbuk gergaji, serutan kayu.